2004
DOI: 10.1007/s00204-004-0551-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ciprofloxacin on joint cartilage in immature dogs immediately after dosing and after a 5-month treatment-free period

Abstract: A study in young beagle dogs was performed in which the animals were treated for 2 weeks with ciprofloxacin at oral doses of 0, 10, 30 or 90 mg/kg per day. Immediately after treatment half of the number of animals were killed and all weight-bearing joints were subject to a thorough gross and histopathological investigation, including special staining of the cartilage matrix, and immunohistochemistry as well as electron microscopy. The remaining animals were maintained for an additional 5-months treatment-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…Experiments with ciprofloxacin-exposed beagle pups documented evidence of erosions of the weight-bearing articular joint surface as long as 5 months after therapy, despite resolution of joint symptoms that occurred at the time of dosing in these animals. 16 These gross anatomic and histologic data concerning articular cartilage, as well as histologic data documenting abnormalities of the epiphyseal cartilage at the highest doses of trovafloxacin and ofloxacin tolerated in rats, 17 prompted concerns that a better understanding of risk associated with fluoroquinolone use in children would require evaluation of children well beyond the period of exposure. Although animal data strongly supported that fluoroquinolone-related damage to cartilage would be evident during or immediately after drug exposure, it was reasoned in designing the levofloxacin pediatric program that clinically apparent, drug-related injury to joint cartilage or to the epiphyseal plate in children could take months to manifest.…”
Section: Figurementioning
confidence: 99%
“…Experiments with ciprofloxacin-exposed beagle pups documented evidence of erosions of the weight-bearing articular joint surface as long as 5 months after therapy, despite resolution of joint symptoms that occurred at the time of dosing in these animals. 16 These gross anatomic and histologic data concerning articular cartilage, as well as histologic data documenting abnormalities of the epiphyseal cartilage at the highest doses of trovafloxacin and ofloxacin tolerated in rats, 17 prompted concerns that a better understanding of risk associated with fluoroquinolone use in children would require evaluation of children well beyond the period of exposure. Although animal data strongly supported that fluoroquinolone-related damage to cartilage would be evident during or immediately after drug exposure, it was reasoned in designing the levofloxacin pediatric program that clinically apparent, drug-related injury to joint cartilage or to the epiphyseal plate in children could take months to manifest.…”
Section: Figurementioning
confidence: 99%
“…In 1977, Ingham et al reported on arthropathy of weight-bearing joints in juvenile animals after postnatal exposure to narrow-spectrum quinolones (5). This effect has also been observed in animal experiments with newer fluoroquinolones (6,7). Therefore, they are generally avoided during pregnancy although studies have not shown any significant risk of cartilage damage in children (8).…”
mentioning
confidence: 97%
“…However, they are contraindicated for children and adolescents and during pregnancy and nursing due to the potential for joint cartilage lesions as found in immature animals (22,23). Quinolone-induced chondrotoxicity in juvenile animals of multiple species has been demonstrated and shown to be irreversible under experimental conditions (5,24), dose dependent (19), and developmental phase (age) specific (22,23,26). The relevance of those observations for humans is still unclear (3).…”
mentioning
confidence: 99%